Assessment of sustainable and biodegradable agricultural substrates for eminence production of cucumber for kitchen gardening - Mubeen Sarwar; Sumreen Anjum; Muhammad Arslan Khan; M. Saleem Haider; Sajid Ali; M. Kaleem Naseem (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Different agricultural substrates were evaluated for growth and productivity of cucumber under pot culture for kitchen gardening. Methods Several agricultural substrates such as leaf compost, compost, perlite, and coconut compost were used in with silt in several combinations. Seeds were sown in plastic pots of 9-L capacity and filled with growing substrates in various combinations. The study consisted of eight treatments; each treatment had four replicates. Results Use of different growing media alone or in combination significantly enhanced plant growth and productivity, compared to control. Results showed that maximum germination, plant growth, emergence percentage, gas exchange attributes, shoot/root length, shoot fresh and dry biomass, root fresh and dry biomass, no. of leaves, leaf mineral contents, and chlorophyll concentration and yield was noted in the plants grown in leaf compost + perlite + silt (1:1:1) media combination. In case of proline contents, all treatment combinations showed non-significant; but, NPK status varied because of the presence of organic matter in substrates that ultimately enhanced the nutrient uptake of cucumber plants. Conclusions Although all media either alone or in combination positively influenced different studied parameters of cucumber, but, leaf compost + perlite + silt (1:1:1) combination was the best. Therefore, leaf compost + perlite + silt (1:1:1) media combination could be considered suitable for the cucumber cultivation in the form of kitchen gardening.